Competencies of murabbis - Mahmad Robbi, Ahmad Akram; Md Yusnan, Mohammad Baihaqi; Md Hashim, Noraini; Wan Muhammad, Ramizah (Islamic Book Trust, 2024)
This chapter aims to explore essential aspects that a mentor (murabbi) should master. To become a proficient mentor, there is a need for a comprehensive understanding, as the role extends beyond delivering speeches in usrah sessions. Instead, mentors must navigate various elements that are applicable in reallife situations, as being a mentor is not confined to usrah alone. The effectiveness of mentors lies in their consistent embodiment of specific qualities, including their presence, character, and personality.